2008
DOI: 10.4049/jimmunol.181.1.494
|View full text |Cite
|
Sign up to set email alerts
|

MEK1/2 Induces STAT5-Mediated Germline Transcription of the TCRγ Locus in Response to IL-7R Signaling

Abstract: The IL-7R plays an essential role in γδ T cell development by inducing V-J recombination of the TCRγ locus through STAT5. Although tyrosine residues in the intracellular domain of the mouse IL-7R α-chain (IL-7Rα) have been implicated in STAT5 activation, it is still unknown whether they are essential for γδ T cell development. In this study, we showed that those IL-7Rα tyrosine residues are not essential for γδ T cell development, because phenylalanine replacement of four intracellular tyrosine residues (IL-7R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…TL1A signaling through DR3 is unlikely to directly induce STAT5 activation, but may enhance STAT5 activity indirectly. MEK and ERK kinases have been found to phosphorylate STAT5 (68, 69), and NF-kB and STAT proteins can bind coordinately to the promoters of a number of genes, including TLR2 (70), FcɛRII (71), and NOS2 (72). The IL-9 promoter contains binding sites for NF-κB and STAT5 making such transcriptional coordination possible (17, 73).…”
Section: Discussionmentioning
confidence: 99%
“…TL1A signaling through DR3 is unlikely to directly induce STAT5 activation, but may enhance STAT5 activity indirectly. MEK and ERK kinases have been found to phosphorylate STAT5 (68, 69), and NF-kB and STAT proteins can bind coordinately to the promoters of a number of genes, including TLR2 (70), FcɛRII (71), and NOS2 (72). The IL-9 promoter contains binding sites for NF-κB and STAT5 making such transcriptional coordination possible (17, 73).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is reported that dual-specificity kinases phosphorylate various target proteins, including transcription factors in addition to downstream kinases (39). A recent study reported that MEK1 associates with STAT5 and induces its tyrosine phosphorylation and DNA binding activity (40). The fact that activated nuclear MEK1 reduces the transcriptional activity of PPAR␥ by associating with it, followed by a rapid nuclear export of the complex also supports the unexpected function of MEK1 for MyoD phophorylation in the nucleus (41).…”
Section: Discussionmentioning
confidence: 83%
“…Ali and Sayeski (23)); pGEX-STAT3 (a gift from Drs. Cao and Cheh Peng (24)); and pGEX-STAT5A (amino acids 494 -793) (a gift from Dr. Ikuta (25)). pGEX-STAT5A-Y694F was obtained by sitedirected mutagenesis using the QuikChange kit (Stratagene) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%